Elucidating the roles of t-helper and t-regulatory cells in sarcoma patients / Sarmini Munisamy - Sarmini, Munisamy (2019)
Tumour cells can create microenvironments that suppress effective anti-tumour activity and interact with host defence mechanisms to support tumour development. The immune system is known to inhibit tumour growth. However, some immune cells could promote tumour growth; i.e. T-regulatory (Treg) cells which play a vital role in tumour promotion and progression. Sarcomas are heterogeneous tumours of connective tissues which depend on angiogenesis for growth and metastasis, with slow progression and local aggressiveness. Those younger than 20-years old are more susceptible to sarcoma, which accounts for 1% of adult cancers; 11% of young adult cancers and 15% of childhood cancers. 50% of sarcoma patients succumb to metastasis during disease progression. This study aims to elucidate the mechanism(s) of sarcomas’ modulation of the host immune system by studying the T – helper cells (Th), Treg cells, and associated cytokines. Peripheral blood leucocytes (PBL) from sarcoma patients were used for flow cytometry analysis, gene expression studies, and analysis of cytokines. Flow cytometry analysis showed a reduction in the total population of CD4+ T-lymphocytes and Treg (CD4+CD25+FoxP3+ ) in sarcoma patients compared to healthy volunteers, but only the former was statistically significant (p < 0.05). PBL from sarcoma and healthy volunteers were cultured in the presence of mitogen for cytokine analysis as plasma levels of cytokines were almost undetectable. Tumour necrosis factor-alpha (TNFα), interferongamma (IFNγ) (p < 0.05), interleukin-17A (IL-17A) were markedly decreased in sarcoma patients’ PBL compared to healthy volunteers. LAP-transforming growth factor-beta1 (LAP-TGF-β1) was significantly reduced (p < 0.05) in sarcoma patients compared to healthy volunteers despite giving higher yield. The quantitative polymerase chain reaction (qPCR) array used was annotated with primers for 84 genes involved in the iv differentiation of CD4+ T-lymphocytes. qPCR analysis showed differential expression (p < 0.05) of five important genes involved in T-cell differentiation, namely homeobox A10 (HOXA10), C-C chemokine receptor type 3 (CCR3), GATA3, prostaglandin D2 receptor (PTDGR2) and thymocyte selection-associated high mobility group box (TOX) genes. HOXA10 expression was significantly (p < 0.05) upregulated in sarcoma patients whilst expressions of CCR3, GATA3, PTDGR2 and TOX were distinctly reduced (p < 0.05). Expression of these genes with two others [T-cell-specific T-box transcription factor T-Bet (TBX21) and tumour necrosis factor superfamily member 11 (TNFSF11)] were validated using real-time polymerase chain reaction (RT-PCR) and it showed upregulation (p > 0.05) of HOXA10 and TBX21 expression in sarcoma patients. Meanwhile, GATA3 and TNFSF1 expression were down-regulated in sarcoma patients. In conclusion, Th cells and its associated cytokines were reduced in sarcoma patients compared to healthy volunteers. This finding suggests possible suppression of the host immune system in sarcoma patients, contributing to ineffective anti-tumour immune responses. This hypothesis is further supported by the imbalance between the numbers of Th and Treg cells (p > 0.05) in sarcoma patients in this study. Expression of some genes responsible for the development and differentiation of CD4+ T-cells were also differentially expressed in sarcomas. Further studies are essential to conclude if the regulation of these genes in immune cells has any significant impact on survival and progression of sarcomas.